Effectiveness of Smartphone Application in Improving Knowledge on Under-Five Childhood Immunization Schedule amongst Parents in Selected Nurseries - Rusli, Mohammad Farhan; Mohd Zulkefli, Nor Afiah; Juni, Muhammad Hanafiah (IIUM Medical Journal Malaysia, 2020)
Introduction: Knowledge on under-five childhood immunization has been identified as a key factor in determining understanding and compliance to the schedule. Understanding the current levels of knowledge and introducing a health intervention to improve the level will benefit the population to be healthier and reduce morbidity. Materials and Method: A quasi-experimental study was conducted in nurseries in Putrajaya and Cyberjaya, Malaysia from January 2016 to January 2018. 98 respondents from Putrajaya were given the technology based intervention and 98 from Cyberjaya were the wait-listed control group. Respondents answered a validated, self-administered questionnaire at baseline, immediate post-intervention and 3 months post-intervention that were specifically targeted to examine their levels of knowledge on under five childhood intervention. Results: Data was analysed using Statistical Package for Social Science (SPSS) Version 23. The level of knowledge at baseline was 58.9% for the intervention group and 61.7% for the control group with no significant difference between both groups (p=0.651). Immediate post intervention showed a significant difference (p<0.001) between the intervention group (97.7%) and control group (54.9%). As for 3 months post-intervention the intervention group was 95.5% and the control was at 85.1% (p<0.001). Conclusion: The level of knowledge improved after receiving the health intervention module and was effective in the increasing of knowledge among the respondents. However, there are still gaps in research that must be addressed in future studies to help further improve knowledge on under-five childhood immunization schedule.